Evaluating the Excellent Class Program Using the CIPP Model: Enhacing Islamic Education Quality in the Era of Global Transformation - Alamsyahbani, Alamsyahbani; Risnita, Risnita; Istofa, Dian Nisa (JURNAL AL-TANZIM, 2026)
This study aims to analyze Islamic education management, specifically the effectiveness of the management of the excellent class program in a state madrasah, using the CIPP (Context, Input, Process, Product) Model as an evaluation framework. A qualitative descriptive approach was used to gain a comprehensive understanding of the program’s planning, implementation, and outcomes in improving the quality of Islamic education. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive analysis model. The results indicate that the excellent class program, implemented for 2 years, aims to respond to the demands of globalization by integrating the national and Cambridge curricula. Program implementation is supported by qualified human resources, structured curriculum planning, and the institution’s commitment to quality improvement. However, the evaluation also identified several areas for improvement, such as consistency in program implementation, optimization of learning facilities, and systematic monitoring of academic processes. The learning program is implemented through extracurricular, co-curricular, and intracurricular activities that strengthen students’ academic competencies and Islamic character. Overall, this study provides evaluative insights into the management of the excellent class program in a state madrasah and recommends strengthening sustainable quality management.